Action of the chemical agent fipronil (active ingredient of acaricide Frontline (R)) on the liver of mice: An ultrastructural analysis - Ferreira, Mateus [UNESP]; De Oliveira, Patricia Rosa [UNESP]; Denardi, Sandra Eloisi [UNESP]; Bechara, Gervasio Henrique [UNESP]; Camargo Mathias, Maria Izabel [UNESP] (Wiley-Blackwell, 2012)
Fipronil, active ingredient of the acaricide Frontiline (R), is a phenyl-pyrazolic derivative, and its efficacy in the elimination of several plagues, even in low concentrations, has already been demonstrated; however, its effect on nontarget organisms has not been thoroughly explained. In this sense, the objective of this study was to evaluate the effects of different dosages of fipronil on the liver of mice in artificial conditions. Results showed that the animals exposed to fipronil present significant ultrastrucutural changes in hepatic cells with evident cellular and cytoplasm disorganization in hepatocytes characterized by an increase in the number of organelles, mainly mitochondria and rough endoplasmic reticulum, organelles that, in the case of the exposed animals, were probably responsible for the enzymes' synthesis that have the function of inactivating the toxic metabolites. A fat accumulation in the hepatocytes' cytoplasm (steatosis) was observed, in addition to extended vacuolated areas, mainly in regions next to the cell nucleus. Alterations observed in the nuclei of the hepatocytes pointed out cell death processes. Moreover, Kupffer cells increased in number (hyperplasia) suggesting an increase in the phagocytic activity of the liver in the exposed animals. Microsc. Res. Tech., 2011. (c) 2011 Wiley Periodicals, Inc.
Keywords: Pesticide; hepatocytes; nontarget organisms; Ultrastructure; MET